The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1051/rnd:2004053
|View full text |Cite
|
Sign up to set email alerts
|

Biopeptides of milk: caseinophosphopeptides and mineral bioavailability

Abstract: -The biological and physiological activities of milk proteins are partially attributed to several peptides encrypted in the protein molecules. These peptides can be liberated by enzymatic digestion in vitro and in vivo. Among the biologically active molecules, phosphorylated peptides (caseinophosphopeptides, CPP) are known to exert an effect on calcium metabolism but also on other minerals. While the existing discrepancy on the potential role of CPP on calcium availability has not been clarified, the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 10 publications
0
49
0
1
Order By: Relevance
“…This is probably because the concentration does not necessarily correlate with the bioavailability of Ba. It has been assumed that released phosphopeptides via casein digestion increase the absorption efficiency of Ca and other divalent cations in milk and milk-based foods (Jov ani et al, 2001;Bouhallab and Bougl e. 2004). On the other hand, the major fraction of Ba in plants and animal meat is assumed to be insoluble and have low bioavailability, which probably decreases the Ba/Ca ratios of subadults through weaning (Austin et al, 2013).…”
Section: Ca-standardized Ba Concentrationsmentioning
confidence: 99%
“…This is probably because the concentration does not necessarily correlate with the bioavailability of Ba. It has been assumed that released phosphopeptides via casein digestion increase the absorption efficiency of Ca and other divalent cations in milk and milk-based foods (Jov ani et al, 2001;Bouhallab and Bougl e. 2004). On the other hand, the major fraction of Ba in plants and animal meat is assumed to be insoluble and have low bioavailability, which probably decreases the Ba/Ca ratios of subadults through weaning (Austin et al, 2013).…”
Section: Ca-standardized Ba Concentrationsmentioning
confidence: 99%
“…Phosphate residues, represented as serine esters, constitute the anionic binding site for minerals such as calcium, iron and zinc and form with them soluble salts, increasing their intestinal bioavailability. Bouhallab and Bouglè (40) showed that a purifi ed phosphopeptide (β(1-25)) exhibits a positive eff ect on iron bioavailability in vivo, reporting its effi ciency in the absorption and availability of iron and the mechanism involved.…”
Section: Caseinophosphopeptidesmentioning
confidence: 99%
“…sequence, the "acidic motif", i.e., Ser(P)-Ser(P)-Ser(P)-Glu-Glu (Bouhallab & Bouglé, 2004 (1) = 50 g CHO (2) = (1) + 6 g CNH (3) = (1) + 12 g CNH 57-59 y ♂ T2D: 13 T2D: n.s. effect with (2) and -6% (3) T2D: n.s.…”
mentioning
confidence: 99%